2015
DOI: 10.1128/aem.02303-14
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interindividual Variations Mask Interspecies Variation in the Microbiota of Sympatric Peromyscus Populations

Abstract: bUsing populations of two sympatric Peromyscus species, we characterized the importance of the host species, physiology, environment, diet, and other factors in shaping the structure and dynamics of their gut microbiota. We performed a capture-markrelease experiment in which we obtained 16S rRNA gene sequence data from 49 animals at multiple time points. In addition, we performed 18S rRNA gene sequencing of the same samples to characterize the diet of each individual. Our analysis could not distinguish between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 46 publications
6
56
0
Order By: Relevance
“…However, among closely related primate species, diet obscures the signal of host phylogeny in gut microbial composition. Epidemiological studies in wildlife have elucidated crossspecies transmission of pathogens [64,100], but little is known about the transfer of commensal microbes among co-occurring wild animal populations [28,97]. More comprehensive comparative studies of wild mammal microbiomes are needed to fully resolve the dynamic dietary, physiological, social, and environmental factors that constrain gut microbiome ecology and evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among closely related primate species, diet obscures the signal of host phylogeny in gut microbial composition. Epidemiological studies in wildlife have elucidated crossspecies transmission of pathogens [64,100], but little is known about the transfer of commensal microbes among co-occurring wild animal populations [28,97]. More comprehensive comparative studies of wild mammal microbiomes are needed to fully resolve the dynamic dietary, physiological, social, and environmental factors that constrain gut microbiome ecology and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these comparative microbiome surveys have sampled geographically and ecologically distinct captive or wild populations (but see [14,27,28]). However, captivity alters microbiome composition in mammals [12,[29][30][31], and, when animals are compared across geographic regions, host phylogenetic differences may be confounded by differences in local microbial taxa [15,32].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies performed on nonlaboratory animals have reported similar degrees of variation between individual microbiotas (De Filippo et al 2010, Osei-Poku et al 2012, Hird et al 2014, Baxter et al 2015, which likely refl ects the multitude of environmental and physiological factors which can infl uence microbial assemblages. In the current study a variety of factors which could not be controlled for likely infl uenced the observed inter-individual variation.…”
Section: Microbiota Compositionmentioning
confidence: 97%
“…its genetic structure of highly conserved regions surrounding hypervariable regions thereby allowing the use of universal primers for the study of microbiota in intestinal samples [22,23] . Our primers were designed for highly conserved regions in the two known species, M. musculus and P. leucopus, that surround a region of variability, and were then used to amplify that same region and test whether that amplicon allows species identification between P. leucopus and P. maniculatus using HRM technology.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%